Trauma Tumpul Akibat Kekerasan Terhadap Anak - Rizqi Uswatun Hasanah; Rahmadsyah Rahmadsyah (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Violence against children is any act against a child that results in physical, psychological, sexual, and/or neglect, misery or suffering, including threats to commit acts, coercion, or unlawful deprivation of liberty. Several factors contribute to violence against children, namely the personal factors of the perpetrator and victim of abuse, environmental conditions that support the perpetrator, and the culture they acquire. Blunt trauma (blunt force trauma) is a force injury caused by a blunt object on the surface of the body which results in injuries caused by objects that have a blunt surface such as stones, wood, hammers, fists and so on, which also includes falls from high places, traffic accidents and others. The results of the examination found bruises on the victim with a bluish color on the right upper leg with a length of four centimeters and a width of two point five centimeters, with a distance of nine centimeters above the knee and on the left upper leg on the front side with a length of four point five centimeters and a width of three. point five centimeters, with a distance of twelve centimeters above the knee.